2010
DOI: 10.1007/s00404-010-1726-4
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia, Mycoplasma and Ureaplasma infections in infertile couples and effects of these infections on fertility

Abstract: There is no significant difference between fertile and infertile couples in terms of the prevalence of the above mentioned infections. Accordingly, during the infertility assessment, infertile couples should not be routinely screened for these infective agents without any clinically sound evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
3
20
2
3
Order By: Relevance
“…Exposure to Mycoplasma heat shock proteins, can significantly affect mucosal immune system by the release of cytokines (IFN-A, IL-10 and TNF-A) leading to severe immunopathological conditions associated with infertility. These results are observed in infertile women with infection while such an issue has not been reported in infected fertile women (33,34). This may be due to differences in the types of infertility in women (women with unexplained infertility in comparison with subfertile women in this study).…”
Section: Discussioncontrasting
confidence: 36%
“…Exposure to Mycoplasma heat shock proteins, can significantly affect mucosal immune system by the release of cytokines (IFN-A, IL-10 and TNF-A) leading to severe immunopathological conditions associated with infertility. These results are observed in infertile women with infection while such an issue has not been reported in infected fertile women (33,34). This may be due to differences in the types of infertility in women (women with unexplained infertility in comparison with subfertile women in this study).…”
Section: Discussioncontrasting
confidence: 36%
“…Aunque, otras investigaciones han concluido que las infecciones por CT prevalecen en parejas con infertilidad, pues se había encontrado un 96,8% de positividad en las parejas infértiles estudiadas (35), mientras que otras no han conseguido diferencias significativas entre las parejas fértiles e infértiles en términos de la prevalencia de las infecciones por CT o UU (36).…”
Section: Discussionunclassified
“…Es por ello que algunas investigaciones no recomiendan, durante la evaluación inicial de las parejas infértiles, la detección rutinaria de los mycoplasmas (UU y MH) sin ninguna evidencia clínica, dado a que no es rentable debido a bajas tasas de detección (23,36,44). No obstante, la infección por este microorganismo puede reducir la tasa de éxito de los tratamientos de infertilidad altamente especializados, entre ellos la inseminación artificial intrauterina, la transferencia de gametos, la fertilización in vitro o la inyección intracitoplasmática de espermatozoides; asimismo, podría causar una marcada reducción del desarrollo embrionario temprano posterior a la fertilización in vitro (22).…”
Section: Discussionunclassified
“…No difference was found between fertile and infertile couples in terms of the effects of these infections on sperm parameters and infertility. Moreover, the prevalence of these infections was found to be the same in fertile and infertile groups [132]. Gdoura et al found that the mean values of seminal volume, sperm concentration, sperm viability, sperm motility, sperm morphology, and leukocyte count were not significantly related either to the detection of C. trachomatis D N A o r t o t h a t o f g e n i t a l u r e a p l a s m a or mycoplasma DNA in semen specimens of asymptomatic male partners of infertile couples [65].…”
Section: Trachomatis Coinfections and Male Infertilitymentioning
confidence: 79%